2008
DOI: 10.1248/bpb.31.1755
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Opioids and KATP Channels in Neuroprotective Effect of Postconditioning in Mice

Abstract: The present study was designed to investigate the possible role of opioids and K ATP channels in ischemic postconditioning-induced reversal of global cerebral ischemia and reperfusion (I/R) induced neuronal injury. Mice were subjected to global ischemia by bilateral carotid artery occlusion for 10 min followed by reperfusion for 24 h, to produce neuronal injury. Ischemic postconditioning was induced by three episodes of carotid artery occlusion and reperfusion of 10 s each, immediately after global ischemia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 40 publications
2
33
0
1
Order By: Relevance
“…It has been confirmed that opioid receptors act through the PTX-sensitive G protein signal pathway (35) and the KATP signal pathway (36). In addition, Zhao et al (37) found that opioid receptors promote cell survival and proliferation via the ERK1/2 pathway.…”
Section: Discussionmentioning
confidence: 95%
“…It has been confirmed that opioid receptors act through the PTX-sensitive G protein signal pathway (35) and the KATP signal pathway (36). In addition, Zhao et al (37) found that opioid receptors promote cell survival and proliferation via the ERK1/2 pathway.…”
Section: Discussionmentioning
confidence: 95%
“…7) Further, several recent-reports from our laboratory 8,9) as well as from others [10][11][12] have advocated cerebro-protective role of ischemic post-conditioning. The major advantage of post-conditioning is its clinical feasibility and it has been observed to produce tissue protective effects in various clinical settings.…”
mentioning
confidence: 89%
“…A subsequent study found that mice deficient for the myocardial adenosine A 2A receptor were resistant to ischemic postconditioning (Morrison et al, 2007). Since 2007, an increasing number of autacoid mediators of postconditioning have been described, including bradykinin (Penna et al, 2007;Xi et al, 2008), opioids (Jang et al, 2008;Pateliya et al, 2008;Zatta et al, 2008), TNFa (Lacerda et al, 2009), and sphingosine (Jin et al, 2008;Vessey et al, 2008a,b).…”
Section: B Cardioprotection Through Postconditioningmentioning
confidence: 99%